Networks of schools. - McMeekin, Robert W. (Education Policy Analysis Archives, 2003)
The study proposes: (1) that the institutional climate in schools, which includes formal rules, informal rules, mechanisms for enforcing both kinds of rules, clear objectives and an atmosphere of cooperation and trust, has a strong influence on school performance; (2) that “networks” of schools such as the Accelerated Schools Project in the U.S. and the Fe y Alegría schools in Latin America help improve school performance in a variety of ways, and have been successful in providing good education to disadvantaged children; and (3) that one of the reasons some networks are successful is that they promote the creation of sound institutional environments in member schools. The argument draws on New Institutional Economics and especially on the role of institutions inside school organizations in reducing agency problems and facilitating transactions between actors in school communities. Three examples of networks with a specific orientation toward improving equity—the Matte Schools of Santiago, Chile, the Fe y Alegría schools in multiple Latin American countries, and the Accelerated Schools Project in the U.S.—are presented and analyzed in terms of how they influence intra-organizational institutions.